(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2021)
This paper offers a phenomenological analysis of Heidegger’s account of ’the uncanny’ (das Unheimliche) as it relates to the coronavirus pandemic. It explores how the pandemic has disrupted Dasein’s sense of ’homelike’ (heimelig) familiarity and how this disruption has undermined our ability to be, that is, to understand or make sense of things. By examining our experience of temporality, lived-space and intersubjectivity, the paper illuminates different ways in which the pandemic has left us confused and anxious about our self-interpretations and future projects. The paper concludes by showing how the uncanny is not simply something we feel in times of crisis; it is, for Heidegger, who we are. This means the secure feeling of familiarity that we embodied prior to the pandemic was an illusion all along, that we are not and never have been at-home in the world.